A comparison of two ship performance models against full-scale measurements on a cargo ship on the Northern Sea Route - Li, Zhiyuan; Ryan, Christopher; Huang, Luofeng; Ding, Li; Ringsberg, Jonas; Thomas, Giles (2020)
The present paper introduces the development and verification of two ship performance models which have been implemented in a voyage planning tool designed for Arctic operations of commercial vessels. An ice resistance estimation algorithm for ice-floe conditions is proposed and implemented in the ship performance models. The fuel consumption predicted using both of the models are compared against full-scale measurements collected on a cargo ship on the Northern Sea Route. Two further case studies representing different Arctic transit periods are also investigated. This work found that both models predict ship fuel consumption with good and satisfactory accuracy and identified directions for future efforts. Overall, the demonstrations prove that an Arctic voyage planning tool, combined with ship performance estimates taking into account the effect of ice and other environmental parameters, can facilitate safe and sustainable Arctic shipping.